2020
DOI: 10.1080/13102818.2020.1810591
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular co-morbidity in patients with COPD in Bulgaria

Abstract: Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality worldwide. It is also associated with significant concomitant diseases which affect the disease progression course, and contribute to the exacerbation of health status and overall mortality rate. The aim of this study was to identify the most frequent Cardio-vascular disease (CVD) comorbidities among patients with COPD in Bulgaria and their effect on the hospitalization rate, hospital stay duration and health status. A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…We should note that disease severity may also impact the prevalence of comorbidities. A recent real-world study [55] reported the highest percentage of comorbidities among COPD patients of group D followed by group B. Taking into account that over 80% of COPD patients has accompanied comorbidity [55,56], these effects cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should note that disease severity may also impact the prevalence of comorbidities. A recent real-world study [55] reported the highest percentage of comorbidities among COPD patients of group D followed by group B. Taking into account that over 80% of COPD patients has accompanied comorbidity [55,56], these effects cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…A recent real-world study [55] reported the highest percentage of comorbidities among COPD patients of group D followed by group B. Taking into account that over 80% of COPD patients has accompanied comorbidity [55,56], these effects cannot be ignored. Besides the health impact, comorbidities are also causing an economic impact [57], as shown in some of the articles included in this review [23,25,31,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…As COPD shares risk factors with cardiovascular diseases (CVDs) and tends to impair cardiac function through different mechanisms, such as increased intrathoracic pressure, hypoxia, oxidative stress and systemic inflammation [2,17], cardiovascular morbidity is more frequent in people with COPD than in the general population [18]. Moreover, it has been observed that among patients with COPD, cardiovascular morbidities lead to more hospitalizations and deaths than COPD itself [19].…”
Section: Introductionmentioning
confidence: 99%